Targeted IgA Fc receptor I (FcαRI) therapy in the early intervention and treatment of pristane-induced lupus nephritis in mice. (2nd July 2015) - Liu, C; Kanamaru, Y; Watanabe, T; Tada, N; Horikoshi, S; Suzuki, Y; Liu, Z; Tomino, Y
Summary: The Fc receptor I for IgA (FcαRI) down-regulates humoral immune responses and modulates the risk of autoimmunity. This study aimed to investigate whether FcαRI targeting can affect progression of pristine-induced lupus nephritis. In the first experiment (early intervention), four groups of animals were evaluated: untreated FcαRI/FcRγ transgenic (Tg) mice and Tg mice administered control antibody (Ctr Fab), saline and anti-FcαRI Fab [macrophage inflammatory protein (MIP)-8a], respectively, three times a week for 29 weeks, after being injected once intraperitoneally with 0·5 ml pristane. In the second experiment, antibody injection started after the onset of nephritis and was carried out for 2 months, with similar groups as described above. MIP-8a improved proteinuria, decreased the amounts of glomerular injury markers, serum interleukin (IL)-6, IL-1 and monocyte chemoattractant protein (MCP)-1, and F4/80 macrophages in the interstitium and glomeruli, in both experiments. When MIP-8a was used as early intervention, a decrease in mouse serum anti-nuclear antibody (ANA) titres and reduced deposition of immunoglobulins in glomeruli were observed. This effect was associated with reduced serum titres of immunoglobulin (Ig)G2a but not IgG1, IgG2b and IgG3. Furthermore, pathological analysis showed lower glomerular activity index and less fibronectin in MIP-8a treated mice. This study suggests that FcαRI targeting could halt disease progression and lupus activation by selective inhibition of cytokine production, leucocyte recruitment and renal inflammation. Our findings provide a basis for the use of FcαRI as a molecular target for the treatment of lupus.